Accurately-controlled recovery and regeneration of protic ionic liquid after Ionosolv pretreatment via bipolar membrane electrodialysis with ultrafiltration. (December 2020) - Liang, Xiaocong; Wang, Junyu; Bao, Haizhen; Liu, Hantao
Graphical abstract: Highlights: Membrane-based recovery strategy designed for protic ionic liquid recovery. Controlled regeneration of [TEA][HSO4 ] achieved by divisional recovery of TEA + and SO4 2− . Highest recovery ratios for TEA + and SO4 2− reached 93.7% and 96.4%. Lowest energy consumption for [TEA][HSO4 ] recovery reached 6.2 kwh/kg. Abstract: Efficient recovery and regeneration of ionic liquid is significant for industrial Ionosolv pretreatment. Complicated electrolyte composition restricts the scale-up recovery and application of protic ionic liquid such as triethylammonium hydrogen sulfate [TEA][HSO4 ] in biomass-related research. Recovery of [TEA][HSO4 ] after Ionosolv pretreatment for miscanthus powder was studied using bipolar membrane electrodialysis (BMED) assisted with ultrafiltration (UF) by the divisional recovery of TEA + as TEA and recovery of SO4 2− as H2 SO4 in different BMED compartments. Hence accurately-controlled regeneration of [TEA][HSO4 ] could be realized. Influence of current density and feed concentration of BMED module was studied in detail. In this study, the highest recovery ratio for TEA + and SO4 2− reached 93.7% and 96.4%. The lowest energy consumption of specific [TEA][HSO4 ] recovery was about 6.2 kwh/kg. Insight gained from this study suggests a potentially industrial methodology for complicated protic ionic liquid recovery after biomass processing.